Social rent policy: Choices and trade-offs - Stuart Adam; Daniel Chandler; Andrew Hood; Robert Joyce (Institute for Fiscal Studies (IFS), 2015)
Social housing providers - local authorities and housing associations - fulfil at least three functions: building housing, acting as landlord and delivering subsidised rent levels. This report focuses on the last of these. Specifically, we analyse the consequences for tenants, social housing providers and the exchequer of changing the level of rent charged to tenants in social housing. We do not take a view as to what level is appropriate, or look at wider policy issues in the social housing system. About one-sixth of the population of Great Britain currently live in social housing, down from about one-third in the early 1980s. On average, social tenants have much lower levels of education, employment and earnings than the population as a whole - gaps which widened dramatically during the1980s and early 1990s. The average social rent in England is currently about 96 per week, which is an estimated 40 (30%) below the average market rent that would be chargeable on social properties. But there is wide variation across the country: all of those averages are significantly higher in London and the south-east and significantly lower in the north of England. Two-thirds ofsocial tenants receive further help with the cost of their rent in the form of housing benefit, a means-tested benefit. There have been important changes to social rent policy in England in recent years. Since 2011, rents for most new social tenancies have been allowed to be much higher than previously, under the "Affordable Rent" model which allows rents at up to 80% of market levels. For existing social tenancies, a 10-year period of real annual increases (CPI + 1%) was planned to apply from 2015-16; only for an announcement in the July 2015 Budget that instead mandated four years of 1% annual nominal reductions in social rents from 2016-17. The Budget also announced that higher-income social tenants will have to pay market or "near market" rents from 2017-18, in a policy known as "Pay to Stay". Although housing benefit is better suited than social housing to providing a comprehensive "safety net" for those in need, it is withdrawn as tenants' incomes increase and this can weaken their work incentives. An importantrole played by sub-market rents in social housing is to reduce tenants' reliance on housing benefit and hence the weak work incentives often associated with it. [...]
Keywords: 330